Commodification of Umrah through Social Media: Phenomenological Study on Umrah Pilgrims of Sociosalites in Jakarta - Candra Andanu, Viktry (Golden Ratio of Data in Summary, 2024)
This research aims to find out the religious activities of Umrah pilgrims of socialites in Jakarta commodified through social media and to find out socialite individuals uploading religious activities on social media. In obtaining data in this study, researchers used qualitative methods based on the constructivism paradigm. This paradigm views knowledge as the result of the construction of human thought, not just the experience of facts. In this case humans understand social reality more based on the subject that examines rather than the object under study. The results of this study indicate that there are individual socialite factors uploading religious activities on social media, this study also found two elements of commodification that were implemented, namely Exchange Value and Use Value, and this study found that Umrah, which is traditionally a religious experience, has now been transformed into a culture of Conspicious Consumption.